2020
DOI: 10.1111/nicc.12559
|View full text |Cite
|
Sign up to set email alerts
|

A workforce survey of critical care nurses in the National Health Service

Abstract: Aim To measure key aspects of the critical care nursing workforce across the National Health Service (NHS) and compare these with recommended standards where they exist. Background The provision of high‐quality and safe critical care services is dependent on adequate numbers of highly skilled nurses. Understanding the issues and challenges within critical care services across the NHS is key to future planning and policy in this area. Design A stakeholder‐driven consensus development approach was adopted to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…The overall gap across the UK is 203 wte pharmacists to meet minimum weekday standards. In absolute numbers, this is not a large number of posts, for comparison there are at least 17,615 wte nurses in critical care in England and Wales [ 32 ], however this deficit represents 6 posts for every 10 critical care units in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…The overall gap across the UK is 203 wte pharmacists to meet minimum weekday standards. In absolute numbers, this is not a large number of posts, for comparison there are at least 17,615 wte nurses in critical care in England and Wales [ 32 ], however this deficit represents 6 posts for every 10 critical care units in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the UK, the productivity of nurses has increased by 23% in the last decade, but nurse recruitment has only seen an increase of 1% (The Health Foundation, 2019b). Over this same period, the number of nurses leaving the profession to seek employment elsewhere has also increased (Chen et al, 2019;Nursing Midwifery Council, n.d.;Stone et al, 2006), with critical care being one of the worst affected areas for turnover (Cutler et al, 2021). Although there is currently no specific systematic review investigating the efficacy of burnout interventions for critical care nurses, there are some systematic reviews that include nurses as part of larger groups of healthcare professionals (Aryankhesal et al, 2019;Awa et al, 2010;Zhang et al, 2020).…”
Section: Challenges Of Ptsd and Burnout For Critical Care Nurse Reten...mentioning
confidence: 99%
“…Furthermore, in 2017, more nurses in the UK were leaving the profession than joining it (Nursing Midwifery Council, n.d.). The problem of high turnover has been cited as a dominant contributor to healthcare workforce shortages (Castro Lopes et al, 2017) and is a global issue (The Health Foundation, 2019a), which is especially prevalent in critical care (Cortese, 2012; Cutler et al, 2021; Stone et al, 2006; van Dam et al, 2013). A 2021 meta‐analysis reported that 27% of critical care nurses worldwide were intending to leave critical care nursing (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing the focus on workforce, in the next article in this special issue, Cutler et al 10 report their workforce survey of NHS critical care nurses undertaken in 2017. The aim of this was to assess the current status of the UK critical care workforce and compare this against national standards and earlier survey data.…”
mentioning
confidence: 99%